32.0k views
1 vote
6. Let f(x)=x-2 and g(x) = x^2. Find the value of (fog)(-1).

A. -1
B.9
C.3
D.-3

User Josanne
by
6.6k points

1 Answer

4 votes

Answer:

The answer is option A

Explanation:

f(x) = x - 2

g(x) = x²

In order to find (fog)(-1) we must first find (fog)(x)

To find (fog)(x) substitute the g(x) into f(x) that's for every x in f (x) replace it with

g (x).

That's

(fog)(x) = x² - 2

To find (fog)(-1) substitute the value of x that's - 1 into (fog)(x)

We have

(fog)(-1) = (-1)² - 2 = 1 - 2 = - 1

Hope this helps you

User Deric Lima
by
5.7k points